2004
DOI: 10.1227/01.neu.0000129547.30778.b7
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Cranial Fossa Volume in Patients with Rickets: Insights into the Increased Occurrence of Chiari I Malformation in Metabolic Bone Disease

Abstract: We have found that the volume of the posterior fossa is significantly smaller in children with rickets versus age-matched control subjects. Furthermore, 29% of our study group had an associated CIM. We may hope that these data will aid in the further understanding of the pathophysiology of CIM in cases of metabolic bone disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 21 publications
3
23
0
Order By: Relevance
“…[5][6][7][8][9] These alterations in bone development produce a reduction in both growth velocity and height, with a higher frequency of scoliosis, leg curvature and cranial deformities. [10][11][12][13][14][15][16][17] Some researchers have recently suggested that 5 min per day, 5 times per week for 4 weeks of passive exercises with soft compressions result in increased bone mineral density (BMD) in very low birth weight premature infants. [18][19][20][21] This prospective randomized controlled clinical assay was carried out with the objective of evaluating the effects of a motor physical therapy protocol, 15 min per day, 5 days per week, on bone mineralization in very low birth weight preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] These alterations in bone development produce a reduction in both growth velocity and height, with a higher frequency of scoliosis, leg curvature and cranial deformities. [10][11][12][13][14][15][16][17] Some researchers have recently suggested that 5 min per day, 5 times per week for 4 weeks of passive exercises with soft compressions result in increased bone mineral density (BMD) in very low birth weight premature infants. [18][19][20][21] This prospective randomized controlled clinical assay was carried out with the objective of evaluating the effects of a motor physical therapy protocol, 15 min per day, 5 days per week, on bone mineralization in very low birth weight preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…The posterior fossa volume in this case was 117.9 cm 3 . This volume is well below aged-matched controls (11- to 15-year-olds) which were 123–173 cm 3 with a mean of 148 cm 3 in one study [4. ]…”
Section: Case Reportmentioning
confidence: 84%
“…The points were counted and a volume calculation was made from the formula: posterior fossa volume = ( t )( Ap ) 2 (Σ Pi ), where t is the distance between the axial slices in cm, Ap is the anatomic distance between the dots of the grid, and Σ Pi is the total number of dots counted on the axial slices. The limits of the posterior fossa were that of what Tubbs et al [4] described in their calculations of posterior fossa volumes in children with rickets. The posterior fossa volume in this case was 117.9 cm 3 .…”
Section: Case Reportmentioning
confidence: 99%
“…3 Rickets may be associated with a variety of cranial bone disorders -craniosynostosis and the presence of cerebellar tonsillar descent being the most notablethat can result in an increase in intracranial pressure. [4][5][6][7][8][9][10] In our patient there was a suspicion of intracranial hypertension associated with XLH. Unfortunately, a lumbar puncture with measurement of the opening pressure could not be performed, as this procedure is considered to be dangerous in patients with an existing cerebellar tonsillar descent.…”
Section: Discussionmentioning
confidence: 99%